The Correlation Between Motivation and Self-Care Mangement Among Leukemia Patients Based on Orem's Theory - Bakar, Abu; Pradanie, Retnayu; Kurniawati, Ninuk Dian; Zahra, Naili Raudiatus (Universitas Airlangga, 2023)
Introduction: Leukemia is one of the most diagnosed types of cancer and a cause of death worldwide. Patients who experience severe side effects of cancer treatment tend to experience less than optimal self-care management. Leukimia patients in treatment often complain of fatigue, weakness, lack of energy, and nausea which hinder them in self-care management. The purpose of this study was to determine the relationship between motivation and self-care management. Methods: This study used an analytic descriptive research design with a cross sectional approach. Population on this research were members of Chronic Granulocytic Leukemia (it is known as